Stability and predictive value of anti-JCV antibody index in multiple sclerosis: A 6-year longitudinal study - Hegen, Harald (PLoS One, 2017)
BACKGROUND: Risk of natalizumab-related progressive multifocal leukoencephalopathy is associated with the presence of anti-JC-virus (JCV) antibodies. OBJECTIVE: To investigate the longitudinal evolution of anti-JCV antibody index and to determine the predictive value of baseline anti-JCV antibody index for long-term stability of anti-JCV antibody status. METHODS: MS patients from the MS centre of Medical University of Innsbruck, who had serum sampling for a time period of 4–6 years at intervals of 6±3 months, were included in this retrospective, longitudinal study. Anti-JCV antibody serological status and index were determined by 2-step second-generation anti-JCV antibody assay. RESULTS: 154 patients were included in this study. Median follow-up time was 63.7 months, with median 11 samples available per patient. At baseline, 111 (72.1%) patients were anti-JCV antibody positive. Baseline anti-JCV antibody index significantly correlated with age (R = 0.22, p = 0.005); there was no difference with respect to sex, disease duration or previously used disease-modifying treatment. During follow-up anti-JCV antibody status changed from negative to positive or vice versa in 17% of patients. In seronegative patients at baseline, baseline anti-JCV antibody index was significantly lower in those remaining seronegative at follow-up compared to those converting to seropositivity (median 0.16 vs. 0.24, p = 0.002). In seropositive patients at baseline, index was higher in those remaining seropositive compared to those reverting to seronegativity (2.6 vs. 0.45, p<10(−7)). Baseline anti-JCV antibody index >0.90 predicted stable positive serostatus (sensitivity 88.7%, specificity 96.5%) and <0.20 stable negative serostatus (sensitivity 61.3%, specificity 97.6%). CONCLUSIONS: Anti-JCV antibody index remained relatively stable over 6-year follow-up with annual serostatus change of ~3%. Baseline anti-JCV antibody index predicted stable negative and stable positive JCV serostatus.